Губерніальна доба в історії музичного мистецтва Чернігівщини: європейський вимір - Васюта, О. (Сiверянський літопис, 2021)
Дослідження пов’язане з обґрунтуванням європейського вектору розвитку музичного мистецтва України, проведене на прикладі музичного мистецтва Чернігівщини «губерніальної доби». Концептосфера «маєткової культури» (Д. Щербаківський) цього періоду сформувала не лише окремі сегменти музичного виконавства, як-то: симфонічного, хорового, сольного вокального та інструментального мистецтва, а й вплинула на поступальний розвиток української культури ХІХ ст. загалом. Відповідно до поставленої мети і завдань головні методологічні підходи ґрунтуються на використанні історико-культурологічного та музикознавчого, причинно-наслідкового, компаративно-аналітичного та системного методів і дають змогу дослідити зразки музичного мистецтва, що стали ознакою прогресивного розвитку культурної сфери регіону. Наукова новизна отриманих результатів полягає в тому, що вперше проаналізовано культуротворчий потенціал «губерніальної доби» в історії музичного мистецтва Чернігівщини в контексті європейських тенденцій, зокрема «бідермаєру». Уперше «губерніальна доба» в історії музичного мистецтва Чернігівщини розглядається як процес культуротворення, що здійснив вагомий вплив як на поширення європейських традицій музичного мистецтва в регіоні, так і на формування музичної культури України ХІХ ст. Важливо, що регіональний аспект мистецького дискурсу дозволяє дослідити і національний, і міжнародний потенціал музичного мистецтва, сформованого на спільноєвропейських традиціях. В історичній ретроспективі музичне мистецтво «губерніальної доби» має позитивні гуманітарні, специфічні виконавські та культурно-естетичні наслідки і є потужним фактором культурної динаміки мистецького розвитку Чернігівщини. The purpose of the article. The article highlights the substantiation of the European vector of development of musical art in Ukraine, conducted on the example of musical art of Chernihiv region in the "gubernial age". The conceptual sphere of "estate culture" (D. Shcherbakovsky) of this period formed certain segments of musical performance, such as: symphonic, choral, solo, vocal and influenced the progressive development of Ukrainian culture of the nineteenth century in general. Research methodology. In accordance with the purpose and objectives, the main methodological approaches are based on the use of historical, cultural and musicological, causal, comparative-analytical and systemic methods and allows to explore unique samples of musical art, which have become a sign of progressive cultural development of the region. The scientific novelty and significance of the obtained results of art research is that for the first time the cultural potential of the "gubernial age" of the history of music art of Chernihiv region is analyzed in the context of European trends in artistic development, in particular "Biedermeier" as an artistic phenomenon of Western European culture of the XIX century. Conclusions. For the first time in the history of music art of Chernihiv region of the "gubernial age" is considered as a process of artistic culture, which had a significant impact on the spread of European traditions of music in the region and on the formation of a holistic picture of Ukrainian music culture of the XIX century. It is important that the regional perspective of artistic time and space allows to explore both the national and international potential of musical art, formed on the common European traditions of intercultural communication. In historical retrospect, the musical art of the gubernial age has positive humanitarian, specific musical-performing and cultural-aesthetic consequences and is a powerful factor in the cultural dynamics of artistic development, prolonged at different stages of historical development of Chernihiv region.